Enhancing students' reading comprehension using collaborative strategic reading : a case study with groups eighth and ninth graders from Cindea 28 millas - Vargas Cortés, Alisson Judicxa 1996-
To address the challenge of enhancing English reading skills among 8th and 9th-grade students at CINDEA 28 Millas, the study's approach to this problem was to analyze the effect of using collaborative strategic reading (CSR). This investigation employed a convergent parallel design that utilizes a mixed-method approach, and there were four main instruments in this research: a pretest, a posttest, an observation checklist, and a questionnaire. During the implementation, the pretest revealed a deficiency in students' performance, which urged the need to address the problem. The posttest that assessed students' achievement showed significant improvements in students' grades. The observation checklist was also developed to identify students' behaviors, finding positive results on learners' participation and adverse outcomes when playing the CSR roles. The last instrument was the questionnaire used to identify students' perceptions about the use of CSR. Most students had a positive experience with CSR, enjoying collaborative work and finding it motivating for their classmates. These results give insights into the effectiveness of CSR as a powerful teaching approach that facilitates active learning and academic success for students. The study proposes several recommendations to enhance CSR in English language teaching, which include expanding the sample size and developing CSR-based lesson plans for different grade levels. These recommendations collectively contribute to improving the outcomes of CSR in language classrooms.